P491Transcriptional regulatory roles of G-quadruplex DNA in promoters of genes involved in beta-adrenergic signaling pathway. (15th July 2014) - Zhou, W; Vilar, R; Ying, L; Harding, SE
Abstract: Background: G-quadruplexes (G4s) are four-stranded DNA secondary structures involved in a diverse range of biological processes. We have previously revealed that G4s are important in cardiac function-related genes and pathways. In the beta-adrenergic receptor signaling pathway, which is directly involved in heart failure (HF), conserved G4s have been found in the promoter of ADRB1 and ADCY5. We hypothesize that by targeting these conserved promoter G4s using synthetic G4-binding ligands, we can inhibit downstream gene expression as an alternative genetic approach for the treatment of HF beyond β-blockers. Methods: Promoter fragments of rat Adrb1 and Adcy5 were amplified from rat genomic DNA by PCR, and inserted into the pGL4.10 luciferase vector. Site-directed mutagenesis was used to disrupt G4-forming sequences. Neonatal rat cardiomyocytes (NRCMs) were isolated from ventricles of 1-3-day-old pups, and grown for 16hrs prior to transfection. Transfected NRCMs were incubated with/without 100μM TMPyP4, a general G4-binding ligand, for 48hrs. Promoter activity differences were measured by dual-luciferase assays. Endogenous Adrb1 and Adcy5 mRNA changes in response to TMPyP4 were determined by real-time PCR. All experiments were done in triplicates for 2-3 repeats. Results: When treated with TMPyP4, the downstream luciferase activity decreased by 24.6% in Adrb1 promoter and 34.6% (P=0.001, n=3) in Adcy5 promoter. Endogenous Adrb1 and Adcy5 mRNA levels decreased significantly in response to TMPyP4 (decreased by 57.2%, and 58.5%, P<0.0001, n=3, respectively). The mRNA of housekeeping Gapdh, which does not contain conserved promoter G4, changed little (P=0.7, n=3). In rat Adcy5 promoter, disruption of the 1st(+1154 to +1185bp), 2nd(+601 to +624bp), 4th(-159 to -136bp), or 5th(-383 to -356bp) G4-forming sequence all induced significant transcription inhibition in response to TMPyP4 (activities decreased by 97.9%, 91.3%, 95.6%, and 95.8% respectively). However, when the 3rd (-82 to -35bp) Adcy5 promoter G4 was disrupted, TMPyP4-induced inhibition effect was not observed. Conclusion: When stabilised by the general G4-binding ligand, conserved G4s in promoters of Adrb1 and Adcy5 can be used as targets to inhibit downstream gene transcription and translation as expected. This may provide certain cardiac protective effects in the progress of HF. In the case of Adcy5, only the 3rd G4 acts as a strong repressor, while other G4s act as activators. Thus, the actual structure and function of G4s need to be investigated individually to guide the design of more specific G4-binding ligands with improved inhibition effects.